# Adv Alegbra HW Solutions 94 - 94(iii We prove that f g = f...

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 94 (iii) We prove that ( f g ) = f g + f g by induction on deg( f ) (of course, the equation holds when f = 0). The base step deg( f ) = 0 has been done in part (ii). For the inductive step, write f (x ) = ak x k + h (x ), where h (x ) = 0 or deg(h ) < k = deg( f ). If h (x ) = 0, then ( f g ) = ak x k bn x n ak bn x n +k = = (n + k )ak bn x n +k −1 = k ak bn x n +k −1 + = kak x k −1 n ak bn x n +k −1 bn x n + ak x k n bn x n −1 = (ak x k ) g (x ) + ak x k g . If h (x ) = 0, then ( f g ) = (ak x k + h (x ))g (x ) = ak x k g ( x ) + h ( x ) g ( x ) = ak x k g (x ) + D (hg ) = ak x k g (x ) + ak x k g + h g + hg = ak x k + h g + (ak x k + h )g = f g + fg . (iv) We prove that ( f n ) = n f n −1 f by induction on n ≥ 1. If we deﬁne f 0 to be the constant function 1, then the base step holds. For the inductive step, f n +1 = fn f = fn f + fn f = (n f n −1 f ) f + f n f = (n + 1) f n f . 3.37 Assume that (x − a ) | f (x ) in R [x ]. Prove that (x − a )2 | f (x ) if and only if (x − a ) | f in R [x ]. ...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online